A Study on Performance Effects of Standard and Stabilized He-Ne Lasers in an Interferometric Measurement System - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2016)
Stabilized He-Ne lasers are commonly utilized in interferometric systems, and provide easy and accurate results. The main reason for their extensive use is their output beam's strength and stability. However, these are relatively high in cost. In interferometric measurement systems, standard He-Ne lasers can also be used. This type of lasers has a lower cost, but their output beam strength can fluctuate in time. And this in turn adversely affects the measurement performance. In this study, a standard He-Ne and a stabilized He-Ne lasers were used in the same measurement system. The measurement errors caused by the fluctuation of the output beam of the standard He-Ne laser are minimized by using a video processing technique. When the obtained results were compared with the ideal values, the relative error for the system with the stabilized He-Ne laser was recorded as 0.2%, while for the system with the standard He-Ne laser a relative error rate of 0.3% was achieved. When the results are analyzed, it is evident that in measurement systems with a standard He-Ne laser, the system performance can be boosted with a video processing technique, and that its results can achieve values closer to the performance of stabilized He-Ne lasers.
Keywords: DISPLACEMENT; RESOLUTION